Pengembangan model pembelajaran Discovery Learning pada madrasah melalui media aplikasi Kahoot terintegrasi Google Classroom (Studi di MI NU Islahussalafiyah Gebog Kudus) - Kamaludin Irsyad; Maslikhah Maslikhah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2022)
This study aims to: (1) Know the results of the identification of needs analysis for the development of the Discovery Learning learning model through the Kahoot application media integrated with Google Classroom in class 5 on Humans and the Environment at MI NU Islahussalafiyah Gebog Kudus, (2) Know the stages in the development of the Discovery Learning learning model through Google Classroom integrated Kahoot application media in class 5 Human and Environment material on student learning outcomes at MI NU Islahussalafiyah Gebog Kudus, (3) Knowing the effectiveness in developing Discovery Learning learning models through Google Classroom integrated Kahoot application media in class 5 Human and Environment material on student learning outcomes at MI NU Islahussalafiyah Gebog Kudus. The type of research in this thesis is a research and development approach. In this study modified into 3 main stages, namely; (1) Preliminary stage (research); (2) The design and validation stages; (3) Limited scale trial phase (dissemination) to produce the final model as final product and publication. Testing the data using the t-test. The results of the research in this study show that: (1) it has fulfilled the needs analysis for the development of discovery learning learning models through integrated google classroom kahoot application media in class 5 human and environmental materials to improve student learning outcomes at MI NU Islahussalafiyah Gebog Kudus; (2) The form of developing a discovery learning learning model through integrated google classroom kahoot application media in class 5 Human and Environment material to improve student learning outcomes at MI NU Islahussalafiyah Gebog Kudus obtained an average total assessment result in the feasibility test on a limited scale against learning media this is 93.6% so that it is included in the category suitable for use; (3) The development of discovery learning learning models through integrated google classrom khoot application media on human and environmental material has an effective and significant effect on student learning outcomes